Sustainable livelihoods of rural community through comprehensive village development programme of Bangladesh Academy for Rural Development - Islam, Md. Shafiqul. 1962- (Comilla : Bangladesh Academy for Rural Development, 2010)
With reference to Comilla District, Bangladesh.
Originally presented as the author's thesis (doctoral)--Banglabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, 2006.
Includes statistical tables.
Includes bibliographical references (p. 191-199).
Social Science
Keywords: Comprehensive Village Development Programme (Bangladesh); Rural development -- Bangladesh -- Comilla District; Rural development -- Bangladesh -- Comilla District -- Statistics; Sustainable development -- Bangladesh -- Comilla District; Sustainable development -- Bangladesh -- Comilla District -- Statistics